The cultural politics of emotion - Ahmed, Sara (Edinburgh University Press, 2014)
This is a bold take on the crucial role of emotion in politics. Emotions work to define who we are as well as shape what we do and this is no more powerfully at play than in the world of politics. Ahmed considers how emotions keep us invested in relationships of power, and also shows how this use of emotion could be crucial to feminist and queer political movements. Debates on international terrorism, asylum and migration, as well as reconciliation and reparation are explored through topical case studies. In this textbook the difficult issues are confronted head on. New for this edition: a substantial 15,000-word Afterword on 'Emotions and Their Objects' which provides an original contribution to the burgeoning field of affect studies; a revised Bibliography; and updated throughout.
Keywords: approches et analyses; capitalisme; corps; discipline; féminisme; histoire et politique; militance; philosophie; queer; ressource en ligne; sciences humaines; systèmes d'oppressions; thématiques; émotions; études culturelles

Contract and domination - Pateman, Carole; Mills, Charles W. (Polity, 2007)
« Contract and Domination offers a bold challenge to contemporary contract theory, arguing that it should either be fundamentally rethought or abandoned altogether. Since the publication of John Rawls's A Theory of Justice, contract theory has once again become central to the Western political tradition. But gender justice is neglected and racial justice almost completely ignored. Carole Pateman's and Charles Mills's earlier books, The Sexual Contract (1988) and The Racial Contract (1997), offered devastating critiques of gender and racial domination and the contemporary contract tradition's silence on them. Both books have become classics of revisionist radical democratic political theory. Now Pateman and Mills are collaborating for the first time in an interdisciplinary volume, drawing on their insights from political science and philosophy. They are building on but going beyond their earlier work to bring the sexual and racial contracts together. In Contract and Domination, Pateman and Mills discuss their differences about contract theory and whether it has a useful future; excavate the (white) settler contract that created new civil societies in North America and Australia; argue via a "non-ideal" contract for reparations to black Americans; confront the evasions of contemporary contract theorists; explore the intersections of gender and race and the global sexual-racial contract; and reply to their critics. »--Page 4 de la couverture.
Keywords: approches et analyses; capitalisme; com5170; contrat social; cours; discipline; histoire et politique; intersectionnalité; patriarcat; philosophie; philosophie politique; pol4212; premier cycle; racisme; rapports de domination; science politique; science politique et droit; sciences humaines; sexisme; système colonial; systèmes d'oppressions; thématiques

L'ONU, alliée des femmes ? Une analyse féministe du système des organisations internationales - Falquet, Jules (Multitudes, 2003)
Cet article analyse la stratégie du système onusien pour neutraliser les mouvements sociaux contestataires en les faisant « participer » à son projet de « bonne gouvernance » mondiale, à travers l’exemple du mouvement féministe latino-américain et des Caraïbes. En étudiant les « politiques de population » des institutions internationales et la question du micro-crédit pour les femmes, on voit comment l’ONU parvient à se présenter comme « alliée » des femmes et à embrigader dans son entreprise une partie du mouvement féministe, alors qu’elle applique des politiques désastreuses pour les femmes, en particulier pour les femmes pauvres du Sud.
Keywords: amérique latine; amériques; approches et analyses; capitalisme; caraïbes; cours; discipline; histoire et politique; inégalités; oppressions institutionelles; philosophie; pol4022; premier cycle; ressource en ligne; régions géographiques; sciences humaines; sexisme; systèmes d'oppressions; thématiques

The death of nature: Women, ecology and the scientific revolution - Merchant, Carolyn (New York : Harper & Row, 1983)
Un examen de la révolution scientifique qui montre comment la vision mécaniste du monde de la science moderne a sanctionné l'exploitation de la nature, l'expansion commerciale sans retenue et un nouvel ordre socio-économique qui subordonne les femmes.
Keywords: approches et analyses; capitalisme; discipline; environnement; histoire; histoire des sciences; histoire et politique; incontournable; patriarcat; philosophie; progrès; projet charge mentale; santé; sciences humaines; systèmes d'oppressions; thématiques; violences; violences envers la nature; violences envers les femmes*; écoféminisme